Frequency of mixed onychomycosis with total nail dystrophy in patients attended in a Guatemalan Dermatology Center - Erick Martinez Herrera (Asociación Colombiana de Infectología, 2018)
Introduction: Onychomycosis are fungal nail infections that can be caused by dermatophytes, non-dermatophytic molds and yeasts, which are capable of breaking down keratin. Mixed onychomycosis are a controversial subject and they are the outcome of the combination of two dermatophytes, dermatophytes/nondermatophytic molds or dermatophytes/yeast. Objetives: To determine the frequency of total dystrophic onychomycosis caused by more than one etiological agent (mixed onychomycosis) in outpatients from a Dermatologic Center in Guatemala and to establish the characteristics associated with this fungal infection. Methods: Prospective observational study from August to December of 2012. Nail samples were obtained from patients with total dystrophic onychomycosis to identify the causal agents by culture in Sabouraud dextrose and Mycosel® agar. Results: 32 of 130 patients had mixed onychomycosis. 68.5% were associated to tinea pedis. The most common association was between T. rubrum + Candida, T. rubrum + M. canis and T. rubrum + opportunist fungi. Conclusions: Mixed onychomycosis represent 25% of the total dystrophic onychomycosis in Guatemala. We observed an important relationship between diabetes and the main association was T. rubrum with Candida spp.